Karmen - March, Guillem, 1979- (Image Comics, 2025)
"Spanish writer and artist Guillem March is best known for his ongoing, extensive work with DC Comics on Batman, Catwoman, and Harley Quinn, takes up his pen for a cutting-edge story about a highly unconventional angel named Karmen and the young woman she takes under her wing when a case of heartbreak strikes hard. Packed with intriguing twists and metaphysical musings, this gorgeously drawn series brings tenderness, heart, and humor to the delicate and difficult matters of life and death that we all face." -- Back cover.